Sliding mode control of the DFIG used in wind energy system - Glaoui, H.; Harrouz, A. (Електротехніка і електромеханіка, 2018)
This paper, presents the application of the direct vector control using the sliding mode control (SMC) on the doubly fed induction
generators (DFIG). The synthesis of the control laws is based on the model obtained by the orientation of the stator flux. The
active and reactive powers that are generated by the doubly fed induction generators will be decoupled by the orientation of the
stator flux and controlled by sliding mode controllers that have been developed. In order to rule on the validity as well as the
performance of this type of adjustment, we will check its robustness by varying some parameters of the machine doubly fed
induction Цель. В статье представлено применение прямого векторного управления с использованием управления режимом
скольжения (SMC) на индукционных генераторах двойного питания (DFIG). Синтез законов управления основан на модели,
полученной с помощью ориентации потока статора. Активные и реактивные мощности, генерируемые индукционными
генераторами двойного питания, разделены ориентацией потока статора и управляются разработанными
контроллерами режима скольжения. Чтобы определить достоверность и эффективность данного типа регулирования,
проверяется его надежность путем варьирования ряда параметров машины двойного питания.